How do you solve this radical equation?y

y - √(y - 10) = 12

y - √(y - 10) = 12

-√(y - 10) = -y + 12 {subtracted y from both sides}

√(y - 10) = y - 12 {divided both sides by -1}

y - 10 = y² - 24y + 144 {squared both sides}

y² - 25y + 154 = 0 {subtracted y and added 10 to both sides}

(y - 14)(y - 11) = 0 {factored into two binomials}

y - 14 = 0 or y - 11 = 0 {set each factor equal to 0}

y = 14 or y = 11 {solved each equation for y}

y = 11 does not check if you put it back in

**y = 14**

*© Algebra House*